Servants, Housewives, Vixens, and the Ever-changing Apron - Bradley, Catherine (Cuizine)

(untitled) (McGill University Library, 2012)
Aprons appear to be innocuous garments, simple in design and straightforward in function. In fact, apron design historically mirrors the overall dress silhouette of the day, changing in response to cultural and social factors such as technological innovation, stock market performance, the women’s liberation movement, and times of political upheaval or economic prosperity. Apron styles, materials, and adornments, and the times and places when and where they are worn, reveal information about apron wearers and their social circumstances. Drawing on contemporary sewing patterns, advertisements, and images, this article explores the history of this often-overlooked garment from Victorian England to present-day Canada.